2015
DOI: 10.1111/add.12860
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term mortality, remission, criminality and psychiatric comorbidity of heroin dependence: 11‐year findings from the Australian Treatment Outcome Study

Abstract: In an 11-year follow-up of patients undergoing treatment for heroin dependence, 10.2% had died and almost half were still in treatment; the proportion still using heroin fell to a quarter, with major depression being a significant predictor of continued use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
73
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(75 citation statements)
references
References 27 publications
2
73
0
Order By: Relevance
“…The current findings regarding depressive status are consistent with somewhat paradoxical findings that major depression increases the likelihood for heroin relapse (Havard, et al, 2006; Teesson et al, 2015), even though depressive symptoms are associated with a greater interest in achieving abstinence and receiving treatment, such as MAT (Avants, Margolin, & McKee, 2000; Mukherjee et al, 2016). Our finding that persons with depressed mood, relative to those with non-depressed mood, were more likely to prefer MAT after detoxification—68% of those preferring MAT met criteria for depressed mood—indicates that depressive symptoms may influence patients’ interest in treatment, and perhaps their recognition of heightened risk.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The current findings regarding depressive status are consistent with somewhat paradoxical findings that major depression increases the likelihood for heroin relapse (Havard, et al, 2006; Teesson et al, 2015), even though depressive symptoms are associated with a greater interest in achieving abstinence and receiving treatment, such as MAT (Avants, Margolin, & McKee, 2000; Mukherjee et al, 2016). Our finding that persons with depressed mood, relative to those with non-depressed mood, were more likely to prefer MAT after detoxification—68% of those preferring MAT met criteria for depressed mood—indicates that depressive symptoms may influence patients’ interest in treatment, and perhaps their recognition of heightened risk.…”
Section: Discussionsupporting
confidence: 83%
“…Major depression and heroin use are highly comorbid (Havard, Teesson, Darke, & Ross, 2006; Teesson et al, 2015), depressive symptoms are associated with lower levels of perceived refusal self-efficacy (Senbanjo et al, 2009) and greater compulsion to use heroin (Lee, Lin, Wang, & Yen, 2016), and major depression is a risk factor for heroin relapse (Hasin et al, 2002; Samet et al, 2013). Therefore, our analysis controlled for depressed mood as well as demographic and drug use factors that are prevalent among heroin users and MAT patients, including unemployment status (Becker, Fiellin, Merrill, Schulman, Finklestein, Olsen, & Busch, 2008; Fischer, Nakamura, Rush, Rehm, & Urbanoski, 2010) and criminal justice involvement (Hakansson & Berglund, 2012; Rastegar, Kawasaki, King, Harris, & Brooner, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies were excluded due to their sampling criteria. For example, many papers from the Australian Treatment Outcome Study included individuals attending needle exchange services who were not treated for their opiate problem (Darke, 2011;Darke et al, 2011;Darke et al, 2009;Teesson et al, 2015;Teesson et al, 2007). There is substantial variation in what the term "older" or "ageing" encompasses and, therefore, the body of evidence for the target population is small, and the majority of studies do not give their reasoning for their choice of age cut-offs.…”
Section: Discussionmentioning
confidence: 99%
“…The burden of disease due to drug use is highest for heroin and other opiates compared to any other illicit drugs (Darke, 2011;Degenhardt and Hall, 2015), and the use of heroin has emerged as an international public health concern within the past decade (Teesson et al, 2015). Long term heroin users have the highest risk of mortality with the average age of death in the early thirties (Darke et al, 2006a) and heroin overdose deaths have been reported among older people in their 50's and 60's (Darke et al, 2006b).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, within periods of methadone treatment there is a swift decline in risk from first to fourth week, followed by a stable trend, whereas after cessation there is a high but quite stable risk during the first four weeks and a progressive decline afterward. This is important because some patients cycle in and out of opioid substitution treatment [46][47][48][49][50] and are therefore exposed to repeated periods of high risk for mortality. Such changes probably mainly reflect changes in risk of fatal overdose, 6 32 but this has not been accurately assessed because only two cohorts reported overdose data specifically.…”
Section: Mortality Risk During Specific Periods In and Out Of Methadomentioning
confidence: 99%